Clustering seasonal performances of soccer teams based on situational score line - Wibowo, Canggih Puspo (Communications in Science and Technology, 2016)
In this research, the basic pattern of seasonal performances of soccer teams is investigated. We propose a clustering method to reveal the seasonal performance. In the proposed method, a new performance indicator called situational score line is used as a feature describing the seasonal performance. It consists of score line, opponent rating, and away rating. Using k-means, the features are clustered into four clusters. Cluster 1, which has a pattern of decreasing performance, is the basic pattern of Italian Serie A and German Bundesliga. Cluster 2 has a stable performance, which is mostly shown in English Premier League, Italian Serie A, and Spanish La Liga. Cluster 3 has the highest competitiveness and is one of the most common patterns in French Ligue 1 and Spanish La Liga. Finally, Cluster 4, which has a rising performance, is the basic pattern of the English Premier League.